2023
DOI: 10.1002/tal.2066
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation of wind loads of kilometer‐scale super tall buildings with typical configurations in veering wind field

Chengdong Feng,
Ming Gu

Abstract: SummaryThe atmospheric boundary layer (ABL), whose total height is about 1–1.5 km, is composed of the atmospheric surface layer (ASL) and the Ekman layer, which typically account for the lower 10% and the upper 90% of the ABL, respectively. The wind veering angle in the Ekman layer can be between 10° and 30°, which may be an important influence factor for the wind‐resistant design of kilometer‐scale super‐tall buildings. Unfortunately, there is very little research on this issue so far due to the difficulty in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is known that LES can simulate near-wall flow and complex flow structures, thereby enhancing the improvement in the resolution of a calculated flow field. Previous research has confirmed the validity and accuracy of LES through comparisons with wind tunnel tests and other numerical simulation methods [20][21][22]. The wind load and aerodynamic performance of the square and trapped building models were estimated by using LES [23,24].…”
Section: Introductionmentioning
confidence: 75%
“…It is known that LES can simulate near-wall flow and complex flow structures, thereby enhancing the improvement in the resolution of a calculated flow field. Previous research has confirmed the validity and accuracy of LES through comparisons with wind tunnel tests and other numerical simulation methods [20][21][22]. The wind load and aerodynamic performance of the square and trapped building models were estimated by using LES [23,24].…”
Section: Introductionmentioning
confidence: 75%